Implementasi Metode Bercerita dalam Peningkatan Kemampuan Berbicara Anak Usia Dini 4-6 Tahun - Aang Andi Kuswandi; Riska Dwi Puspita; Ariyanti Mareta Ismail (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Language is one aspect of early childhood development apart from religion and morals, physical and motor, cognitive, social emotional, and art. In the aspect of language development, it includes 1) understanding language and 2) expressing language. Speaking is part of the way to express language and children's speaking skills are needed as a means of communication for children. Based on the results of initial observations at Mawar Cikalong Kindergarten which showed that the speaking ability of children aged 4-5 years was still low. As an educator who is critical and solution-oriented, the author chooses the storytelling method as an effort to improve the storytelling skills of children aged 4-5 years at Mawar Cikalong Kindergarten. The storytelling method is carried out periodically and continuously with variations using media and not using media. The success rate of speaking ability in children aged 4-5 years in Mawar Cikalong Kindergarten is achieved to be more and better than the initial observation. It can be concluded that the storytelling method is able to improve the speaking ability of children aged 4-5 years in Mawar Cikalong Kindergarten.